2020
DOI: 10.1016/j.media.2020.101691
|View full text |Cite
|
Sign up to set email alerts
|

Generative-based airway and vessel morphology quantification on chest CT images

Abstract: Accurately and precisely characterizing the morphology of small pulmonary structures from Computed Tomography (CT) images, such as airways and vessels, is becoming of great importance for diagnosis of pulmonary diseases. The smaller conducting airways are the major site of increased airflow resistance in chronic obstructive pulmonary disease (COPD), while accurately sizing vessels can help identify arterial and venous changes in lung regions that may determine future disorders. However, traditional methods are… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Numerous studies have shown that CNNs can be successfully applied to real-world laparoscopic videos 22 . Examples include procedural phase and instrument presence detection 23 as well as surgical instrument segmentation 24 . So far only one previous study analyzed surgical skill based on laparoscopic videos 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that CNNs can be successfully applied to real-world laparoscopic videos 22 . Examples include procedural phase and instrument presence detection 23 as well as surgical instrument segmentation 24 . So far only one previous study analyzed surgical skill based on laparoscopic videos 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Arterial and venous separation of the pulmonary vessels have been challenging and initial attempts were based on graph matching and partitioning techniques 56,57 . Nardelli et al 58 proposed a CNN to compute an "arterialness" probability for each vessel location based on cropped image sections of a vessel. Those probabilities were used to further divide the vascular tree in a connected arterial and venous size.…”
Section: Heart-lung Interactionmentioning
confidence: 99%
“…The definition of vascular phenotypes in COPD that can be potentially sensible to remodeling relies on an accurate estimation of the vessel size, particularly in small vessels. This is technically challenging as the CT scanner's resolution compromises the ability to resolve 59 to synthesize real looking CT scans of airway and vessel with known characteristics have been employed to train accurate regressors of vessel and airway morphometric characteristics 60 . This approach has been shown to provide accurate airway and vessel metrics while preserving high precision to variations in imaging protocol (Fig.…”
Section: Heart-lung Interactionmentioning
confidence: 99%
“…We extracted the lung vascular geometry in both inspiratory and expiratory CT scans using a scale-space particle system [34,62] that is implemented in the Teem library [61]. We used the pipeline that is defined in the chest imaging platform [83,102].…”
Section: A1 Pulmonary Vascular Tree Datasetmentioning
confidence: 99%